Language Style’s Effect on Nike Advertisement - Padli Raehan padli; Dias Wahyu Darmalita dias; Isma’ati Anisa anisa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted to describe and analyze the popularity of Nike’s shoes that were used in the advertisement promotions. The theory that is used in this research is Critical Discourse Analysis perspective. This research mainly focused on the word and phrase that was used in the advertisement of Nike shoes and how the advertisement worked to attract the attention of their customers. The analysis of this research is based on a descriptive qualitative method to analyze and to identify three pictures of Nike shoe advertisement promotions. There are three pictures of Nike’s shoe advertisement that are used on their website. The findings and the result of this research are that the Nike brand uses repetition of the front alphabet in their advertisements to attract their customers eye- catchingly. Nike also uses hyperbole to manipulate and influence their customers to buy their product. And the last advertisement is showing a picture that is similar to a human's lungs and there is a caption to show the shoes as important things to make the customer’s body healthy. Nike rarely shows their name product, they just use their symbol on every advertisement. But, most people in the world know that it is Nike's advertisement because Nike is a brand which is very famous in the world.